Pengaruh Pendidikan Kewirausahaan dan Digital Literacy Terhadap Minat Berwirausaha Mahasiswa Dengan Efikasi Diri Sebagai Mediator - Sri Mulyati (Universitas Negeri Surabaya, 2023)
This study aims to examine the effect of entrepreneurship education and digital iteracy on entrepreneurial interest with self-efficacy as a mediating varible. This research is a quantitative research with a survey method, data collection techniques through questionnaires. The population in this study were all 106 students of Economics Education. Hypothesis testing and analysis of respondent data in this study were carried out using path analysis. The results of the study show that there is a positive and significant influence on entrepreneurship education, digital literacy, and self-efficacy on the interest in entrepreneurship. Based on the results and research findings, educational institutions must continue to strive to develop students' interest in entrepreneurship through various programs that increase student motivation to entrepreneurship.